Can the Hydrophilicity of Functional Monomers Affect Chemical Interaction?. (February 2014) - Feitosa, V.P.; Ogliari, F.A.; Van Meerbeek, B.; Watson, T.F.; Yoshihara, K.; Ogliari, A.O.; Sinhoreti, M.A.; Correr, A.B.; Cama, G.; Sauro, S.
The number of carbon atoms and/or ester/polyether groups in spacer chains may influence the interaction of functional monomers with calcium and dentin. The present study assessed the chemical interaction and bond strength of 5 standard-synthesized phosphoric-acid ester functional monomers with different spacer chain characteristics, by atomic absorption spectroscopy (AAS), ATR-FTIR, thin-film x-ray diffraction (TF-XRD), scanning electron microscopy (SEM), and microtensile bond strength (μTBS). The tested functional monomers were 2-MEP (two-carbon spacer chain), 10-MDP (10-carbon), 12-MDDP (12-carbon), MTEP (more hydrophilic polyether spacer chain), and CAP-P (intermediate hydrophilicity ester spacer). The intensity of monomer-calcium salt formation measured by AAS differed in the order of 12-MDDP=10-MDP>CAP-P>MTEP>2-MEP. FTIR and SEM analyses of monomer-treated dentin surfaces showed resistance to rinsing for all monomer-dentin bonds, except with 2-MEP. TF-XRD confirmed the weaker interaction of 2-MEP. Highest µTBS was observed for 12-MDDP and 10-MDP. A shorter spacer chain (2-MEP) of phosphate functional monomers induced formation of unstable monomer-calcium salts, and lower chemical interaction and dentin bond strength. The presence of ester or ether groups within longer spacer carbon chains (CAP-P and MTEP) may affect the hydrophilicity, μTBS, and also the formation of monomer-calcium salts.